(untitled) - Horton, Paul B. (New York, 1980)
This survey focuses on five key concepts to explain sociological principles: function; structure; action; culture; and power. These concepts enable the text to present structural sociology and culture, with student-orientated examples.
Keywords: Sociology,Xã hội học